(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper presents a comprehensive overview of the status and opportunities for wave energy in Australia, drawing on a national report completed in 2024. As the country with the largest wave energy resource in the world, Australia has an important role in the development of a global wave energy industry. This paper reviews the international and domestic landscape, Australia’s resource and market opportunities, as well as the industry, social and environmental context for an Australian wave energy industry. Based on these findings, a series of actions are recommended to catalyse the growth of an Australian industry, and take advantage of the natural advantages the country is endowed with.